A TICT-AIE activated dual-channel fluorescence-on probe to reveal the dynamics mechanosensing of lipid droplets during ferroptosis - Yu, Ao (Elsevier, 2025)
Mechanical forces play a crucial role in cellular processes, including ferroptosis, a form of regulated cell death associated with various diseases. However, the mechanical aspects of organelle lipid droplets (LDs) during ferroptosis are poorly understood. In this study, we designed and synthesized a fluorescent probe, TPE-V1, to enable real-time monitoring of LDs' viscosity using a dual-channel fluorescence-on model (red channel at 617 nm and NIR channel at 710 nm). The fluorescent imaging of using TPE-V1 was achieved due to the integrated mechanisms of the twisted intramolecular charge transfer (TICT) and aggregation-induced emission (AIE). Through dual-emission channel fluorescence imaging, we observed the enhanced mechanical energy of LDs triggering cellular mechanosensing, including ferroptosis and cell deformation. Theoretical calculations confirmed the probe's behavior, showing that high-viscosity media prevented the rotation processes and restored fluorescence quenching in low viscosity. These findings suggest that our TICT-TPE design strategy provides a practical approach to study LDs' mechanical properties during ferroptosis. This development enhances our understanding of the interplay between mechanical forces and LDs, contributing to the knowledge of ferroptotic cell death and potential therapeutic interventions targeting dysregulated cell death processes.